DEVELOPMENT AND VALIDATION OF DYSFUNCTIONAL DAYDREAMING SCALE - Shafiq, Sameera; Hajra Zafar; Nazish Khalid (Journal of Postgraduate Medical Institute, 2023)
Objective: To develop a valid and reliable Dysfunctional Daydreaming Scale (DDS). Methodology: This study aimed to create the item pool for the DDS and was conducted in three phases. In the second phase, 45 items out of a total of 67 items were selected for administration to a sample of 40 individuals, chosen through purposive sampling from Gujrat and Sialkot and ranging in age from 12 to 60 years. In the first phase, semi-structured interviews were conducted with four clinical psychologists and two psychiatrists, as well as ten individuals aged 20 to 60 years. The items were evaluated by five experts in psychology. Results: The Kaiser-Meyer-Olkin measure of sampling adequacy (KMO=0.924) and Bartlett's test of sphericity (x2=6717.842, p<.001) were satisfactory. The exploratory factor analysis identified two factors, "Escapes" and "Emotional Distress," for the DDS with a reliability coefficient of .94 and satisfactory concurrent validity with the MDS (r=.75, p<.01). Conclusions: The DDS is a reliable and valid psychometric test that has been developed locally to evaluate maladaptive thought patterns that may serve as a risk factor for the development of psychiatric disorders.